Pengaruh E-Wom, Trust, Value Co-Creation, dan Brand Image Terhadap Purchase Intention - Ardi Fadilah; Lista Meria (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Purchase intention is an effective indicator to find out how interested consumers are in a product and can influence market potential. This research aims to test and analyze the influence of E-WOM, Trust, Value Co-creation, and Brand Image on Purchase Intention for Converse shoe products. The research approach used in this research is quantitative research. The population in this research is all people who have purchased Converse shoe products. This research uses a non-probability sampling technique using purposive sampling. The sample selection criteria in this study were those who had previously purchased and used Converse shoe products, were aged > 17 years and were in the Jabodetabek area. Questionnaires were collected from 100 respondents, the data was then processed using the multiple linear regression method. Results of data analysis carried out with the help of SPSS tools. Based on the results of this analysis, it is known that partially the E-WOM variable has no effect on Purchase Intention. The Trust variable has a positive influence on purchase intention. The value co-creation variable has a positive effect on purchase intention, and brand image has no effect on purchase intention.